7 secrets to investing like Warren Buffett a simple guide for beginners - Buffett, Mary; Seah, Sean 1981- (Simon & Schuster, 2019)
A complete guide for beginning investors who want to understand how to invest like Warren Buffett. This is one of the first books to showcase both Warren Buffett's Value Investing technique and his life skills and habits for beginning investors. Sustainable results often come from changes in lifestyle and habits; hence, the first section of the book discusses habits that one needs to adopt to be able to invest like Warren Buffett, and prepares readers for a lifelong journey of wealth building. The second section examines specific stock-picking techniques. The authors look at timeless principles as well as latest ideas on where to find great investment ideas, and share specific financial indicators they look for in a good investment. The authors explain valuation principles and techniques that help investors decide when to buy a stock. The techniques are inspired by investor and economist, Benjamin Graham, the 'father of value investing', and are vastly different from the common Wall Street wisdom of trying to time the market. The final section of the book explains how the reader can build and track a portfolio of stocks. Authors encourage readers to follow Warren Buffett's first rule of investing 'Never Lose Money', and explain three important steps that significantly lower risk: - Choose good stocks with low risk - Buy at a good price with margin of safety. - Diversify into a basket of stocks. Questionnaires, charts and graphs help explain techniques and habits simply.